Sustainable SCM Approach as a Branding Strategy on the Hutan Bambu Tourism Object in Bekasi City - Wuwuh Andayani; Aramia Fahriyah; Rochland Yoseph; Dessy Andamisari; Ridfa Chairani (Ilomata International Journal of Management, 2022)
This study was aimed at analyzing the implementation of the Sustainable Supply Chain Management (SSCM) approach as a branding strategy of tourism development of Hutan Bambu in Bekasi city. This study employed a descriptive research method using a qualitative approach. The data sources were primary and secondary data. The techniques of data collection were observation, interviews, and documentation. The interviews were conducted with six informants representing the manager, visitors, local communities, and food sellers in the Hutan Bambu area of Bekasi city. Furthermore, the data were analyzed by using the SSCM approach. The results of the study showed that the branding strategy for developing the Hutan Bambu tourism object can apply several ways. First, it considered SSCM concerns, especially sustainability, marketing-logistics empowerment, market-driven SCM, synchronous SCM, fast response logistics, and network-based resource management. Second, the tourism development was carried out by creating strong branding with the advantages of the Hutan Bambu tourism object, namely by marketing through social media to local and national communities. Third, the development can be done by holding attractive soft skills programs regularly by collaborating with training studios or certain institutions, so they can bring in visitors on a more regular and programmed basis. Fourth, this can also be done by modifying the management system, so the tourists can find alternative tourism objects in the city. Finally, the SSCM approach could be implemented in the development of the Hutan Bambu tourism object, Bekasi by strengthening branding and interesting soft-skills, as well as modifying the management system.